THE FOSSIL VERTEBRATE DATABASE OF THE NATURAL HISTORY MUSEUM OF FLORENCE AND HIGH-RESOLUTION MAGNETIC STRATIGRAPHY IN THE UPPER VALDARNO BASINS, AS A CLUE TO DATE OLD COLLECTIONS (Rivista italiana di Paleontologia e Stratigrafia, 2001)
The well established biochronologic sequence of the Villafranchian Stage in Italy is mainly based on faunal associations from the Upper Valdarno (UV) mostly collected since the late 18 hundreds, and housed in the Natural History Museum of Florence. The old collections were assembled from mostly unidentified stratigraphic levels, and their position possibly reconstructed from the surrounding geologic features. The recent magnetostratigraphic assessment of the sequence marked the earliest finds about 3.0 Ma in themid Pliocene. The end of the Pliocene was recorded by the Olduvai magnetochron in the Matassino and Poggio Rosso sites, and by other sparse assemblages. The Tasso Faunal Unit, assembled in the UV, is assigned to the Pleistocene, yet to be clarified by magnetostratigraphic data. The calibration of old, poorly timed faunas was greatly facilitatedby the computer automated catalogue of the Museum. The possibility of numerous feed-back controls enhanced any contradictory information in fossil collections and made them most fruitful for paleomagnetic calibrations: the Faella fauna and the Faella main outcrop are the ones that will be first re-examined. It is in fact now evidenced the potential role of the catalogue for accomplishing the calibration of old findings timed around the Olduvai chron, with an accuracy depending on the available record of their inferred stratigraphic levels. Numerical dates will make the old collections comparable to the new ones and both fitting into a comprehensive framework of faunal, chronologic, sedimentary evolution of the UV basin, and development in the Plio-Pleistocene climate changes.